Probability weighting and insurance demand in a unified framework - Johannes G. Jaspersen; Richard Peter; Marc A. Ragin (The Geneva Risk and Insurance Review, 2022)
We provide a comprehensive analysis of the impact of probability weighting on optimal insurance demand in a unified framework. We identify decreasing relative overweighting as a new local condition on the probability weighting function that is useful for comparative static analysis. We discuss the effects of probability weighting on coinsurance, deductible choice, insurance demand for low-probability, high-impact risks versus high-probability, low-impact risks, and insurance demand in the presence of nonperformance risk. Probability weighting can make better or worse predictions than expected utility depending on the insurance demand problem at hand.
Keywords: D11; D81; G22; 330; Insurance demand; Probability weighting; Non-expected utility; Comparative statics; Decreasing relative overweighting